Analysis Of Marketing Strategy In The Strategic Business Division Of Government And Institution At Pt Surveyor Indonesia - Syarifah Beanaiaputihati; Raden Roro Ratna Roostika (UNIVED Press, 2025)
The Testing, Inspection, and Certification (TIC) industry plays a crucial role in driving economic growth, especially in an ever-evolving market. PT Surveyor Indonesia’s Strategic Business Division for Government and Institution is a key player in this sector, requiring effective strategies to capitalize on its strengths and address weaknesses to maintain competitiveness. This study aims to analyze both internal and external factors impacting the division’s marketing strategy and to identify the most effective strategic alternatives for its development. A qualitative research approach was employed, using purposive sampling and a descriptive-qualitative methodology. Analytical tools such as the Internal Factor Evaluation (IFE) matrix, External Factor Evaluation (EFE) matrix, Internal-External (IE) matrix, SWOT analysis, and Quantitative Strategic Planning Matrix (QSPM) were used. The results indicate that the division falls under the Growth and Build category in the IE matrix, implying that strategies like market penetration, market development, service diversification, and strategic partnerships are the most effective in strengthening its position in both domestic and global markets. These findings provide key recommendations for enhancing the division’s competitiveness and ensuring sustainable growth in the TIC industry.